2021
DOI: 10.9744/pemasaran.15.2.110-118
|View full text |Cite
|
Sign up to set email alerts
|

Shopping Orientation, Status Consumption and Impulse Buying of Generation X and Y in Purchasing Fast Fashion Products

Abstract: Generation cohorts have different tendencies in purchase behaviors, especially the Generation X and the Generation Y. Although the age gap between these two generation cohorts is not wide, the Generation X has distinctive purchase behaviors that are different from the Generation Y. In the fashion business, the Generation X consumers do not consider the brands in purchasing their clothes, but they calculate the benefits in buying a clothing product. However, the Generation Y consumers consider it as a part of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
1
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 27 publications
1
5
1
3
Order By: Relevance
“…Fast fashion store pricing, such as maintaining constantly good prices and offering a good quality-price ratio significantly influenced all three generations' store satisfaction. While our results suggest that the price seems to be one of the most critical factors influencing consumer satisfaction (Dabija & Băbuț, 2019), from a generational perspective, our findings are contrary to those by Vinoth & Balaji (2015) and Suprapto et al (2021), who suggest that prices have a higher impact on Xers than on Millennials.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…Fast fashion store pricing, such as maintaining constantly good prices and offering a good quality-price ratio significantly influenced all three generations' store satisfaction. While our results suggest that the price seems to be one of the most critical factors influencing consumer satisfaction (Dabija & Băbuț, 2019), from a generational perspective, our findings are contrary to those by Vinoth & Balaji (2015) and Suprapto et al (2021), who suggest that prices have a higher impact on Xers than on Millennials.…”
Section: Discussioncontrasting
confidence: 99%
“…Naturally, members of a generation enjoy similar experiences, having shared behavioral patterns and values, and relating in a unitary way to certain preferences, attitudes, motivations, behaviors, experiences, feelings, emotions, mindsets, etc. (Gurău, 2012;Dabija et al, 2017;Suprapto et al, 2021). A proper understanding of the common aspects influencing consumers' preferences for certain products, such as fast fashion items, may prove essential to targeted approaches by international retailers of the industry.…”
Section: The S-o-r Model and Generational Theorymentioning
confidence: 99%
See 2 more Smart Citations
“…Then, with the influence of the atmosphere in the mall, someone may enter a store and have a look at the store. This study supports the results of the research by Beatty and Ferrel (1998) and Suprapto et al (2021) about shopping enjoyment, so it can be concluded that shopping enjoyment has an effect on in-store browsing because when the customers enjoy shopping, they will have longer time doing in-store browsing.…”
Section: Discussionsupporting
confidence: 89%